Estudo anatômico da artéria torácica interna aplicado à cirurgia cardiovascular - Jorge A HENRIQUEZ-PINO; Walter José GOMES; José Carlos PRATES; Ênio BUFFOLO (Brazilian Journal of Cardiovascular Surgery, 1997)
Com a intensa utilização da artéria torácica interna (ATI) na operação de revascularização do miocárdio, estudamos sua anatomia com a finalidade de esclarecer aspectos morfológicos que possibilitem extender sua utilização e prevenir complicações pós-operatórias. Em 100 cadáveres foram retirados os plastrões esternocostais e injetadas as ATIs com Látex Neoprene. A ATI originou-se diretamente da artéria subclávica em 82,5% e de um tronco comum com outras artérias em 17,5%. O comprimento médio foi de 20,4 ± 2,1 cm e o ponto de terminação mais freqüente foi ao nível do 6º espaço intercostal (e.i.) (52,5%). A forma de terminação se fez como bifurcação em 93% e como trifurcação em 7%. A relação da ATI com a margem esternal foi de 10,3 ± 3,2 mm ao nível do 1º e.i. e 19,2 ± 6,0 mm ao nível do 6º e.i. A ATI está recoberta pelo músculo transverso do tórax numa extensão média de 7,5 ± 2,7 cm e apresenta o ramo costal lateral em 15%. O nervo frênico é anterior à ATI em 70% e posterior em 30%. O estudo forneceu subsídios que podem contribuir para minimizar as complicações pós-operatórias. The internal thoracic artery (ITA) was studied because of its increased utilization in myocardial revascularization surgery due to the excellent long-term results. A review of its anatomical characteristics to clear some morphological aspects was made, aiming to help the extension of its utilization and prevent operative complications. The study was carried out in 100 cadavers; the anterior sternocostal wall of the thorax was removed and the arteries were injected with Neoprene Latex. The ITA originated directly from the subclavian artery in 82.5% and from a common trunk with other arteries in 17.5%. Its lenght was 20.4 ± 2.1 cm in average and the most frequent end point was the 6th intercostal space (52.5%). The end point form was as bifurcation in 93% and as trifurcation in 7%. The relation of ITA with the sternal margins was, on average, 10.3 ± 3.2 mm at the level of first intercostal space and 19.2 ± 6.0 mm at the level of 6th intercostal space. It was covered by the transverse muscle of thorax in a distance of 7.5 ± 2.7 cm long (average) and the lateral costal branch was present in 15%. The ITA was crossed anteriorly by phrenic nerve in 70% and posteriorly in 30%. Informations provided by this study may help prevent complications in ITA dissections and to improve our knowledgement on its anatomical characteristics.